A novel untrained SSVEP-EEG feature enhancement method using canonical correlation analysis and underdamped second-order stochastic resonance - Chen, Ruiquan; Xu, Guanghua; Zhang, Huanqing; Zhang, Xun; Li, Baoyu; Wang, Jiahuan; Zhang, Sicong (Frontiers in Neuroscience, 2023)
Compared with the light-flashing paradigm, the ring-shaped motion checkerboard patterns avoid uncomfortable flicker or brightness modulation, improving the practical interactivity of brain-computer interface (BCI) applications. However, due to fewer harmonic responses and more concentrated frequency energy elicited by the ring-shaped checkerboard patterns, the mainstream untrained algorithms such as canonical correlation analysis (CCA) and filter bank canonical correlation analysis (FBCCA) methods have poor recognition performance and low information transmission rate (ITR). Methods: To address this issue, a novel untrained SSVEP-EEG feature enhancement method using CCA and underdamped second-order stochastic resonance (USSR) is proposed to extract electroencephalogram (EEG) features. Results: In contrast to typical unsupervised dimensionality reduction methods such as common average reference (CAR), principal component analysis (PCA), multidimensional scaling (MDS), and locally linear embedding (LLE), CCA exhibits higher adaptability for SSVEP rhythm components. Conclusion: This study recruits 42 subjects to evaluate the proposed method and experimental results show that the untrained method can achieve higher detection accuracy and robustness. Significance: This untrained method provides the possibility of applying a nonlinear model from onedimensional signals to multi-dimensional signals. Index Terms-motion checkerboard patterns, braincomputer interface, canonical correlation analysis, underdamped second-order stochastic resonance, information transmission rate I. INTRODUCTION rain-computer interface (BCI) is a normal output pathway system that does not rely on the composition of peripheral nerves and muscles, and can directly convert central nervous activities into artificial output [1-3].